Influence of fresh and thermoxidized carotino oil on Cyclic Guanosine Monophosphate (cGMP) in erythrocytes from Sprague dawley rats / Mohd Fakharul Zaman Raja Yahya and Athifah Najwani Shahidan - Raja Yahya, Mohd Fakharul Zaman; Shahidan, Athifah Najwani (Research Management Institute, 2012)
Cyclic guanosine monophosphate (cGMP) is a second messenger molecule involved in the intracellular signalling mechanism which is important in a wide range of cellular process including metabolism, gene expression, cell proliferation and cell death. This study was conducted to determine the effect of fresh (FCO) and thermoxidized carotino oil (TCO) on erythrocyte cGMP levels from Sprague dawley rats. A total of 30 Sprague dawley rats were randomly segregated into three groups: the first of which was placed on a Fresh Carotino Oil (FCO) diet, the second on a Thermoxidized Carotino Oil (TCO) diet and the control group on commercial rat chow only for a period of 6 and 9 weeks. The two oil diets comprised of 20% (w:w) of each oil mixed with commercial rat feed. The enzyme immunoassays, performed in week 6, revealed that the erythrocytes cGMP levels for the FCO and TCO groups were 66.198±3.193 pmol/mL and 61.990±6.318 pmol/mL respectively, and were significantly (p<0.05) lower than the value for the control group, 77.978±10.479 pmol/mL. The assays performed in week 9 revealed the erythrocytes cGMP levels for the FCO and TCO groups to be 66.522±8.194 pmol/mL and 56.842±8.546 pmol/mL respectively which were also significantly (p<0.05) lower than that for the control group, 82.817±6.677 pmol/mL. The results indicate that the presence of antioxidants, such as beta-carotene and tocols in carotino oil may modulate cGMP levels in rats.